Demographic Characteristics, Motivation and Perception of Change as Determinants of Memory Compensation Self-Reports After Acquired Brain Injury - Martin, Sophie; Mooruth, Draushika; Guerdoux-Ninot, Estelle; Mazzocco, Clémence; Brouillet, Denis; Taconnat, Laurence; Trouillet, Raphaël (Frontiers in Psychology, 2021)
Introduction: Individuals with brain injuries experience cognitive and emotional changes that have long-lasting impacts on everyday life. In the context of rehabilitation, surveys have stressed the importance of compensating for memory disturbances to ease the impact of disorders on day-to-day autonomy. Despite extensive research on the nature of neurocognitive impairments following brain injury, few studies have looked at patients’ perceptions of these day-to-day compensations. This study examines these perceptions; in particular, what brain-injured people believe they do to compensate for memory deficiencies in everyday life. It also investigates the determinants of reported compensation strategies (age, gender, perceived stress, change awareness and motivation to succeed). Method: Eighty patients and 80 controls completed the French Memory Compensation Questionnaire, a self-report measure of everyday memory compensation. Five forms of compensation were investigated: External and Internal strategies, Reliance on social help, and investments in Time and Effort, along with two general factors: the degree of importance attached to Success (motivation) and perceptions of Change. Participants also completed measures of demographic and emotional aspects that may affect everyday compensation perceptions. Results: The brain-injured group reported significantly more frequent use of memory compensation strategies than controls, with the exception of External aids. Large effects were observed for Reliance and Effort. Demographic, motivation and perception of change determinants were found to have different effects depending on the compensation strategy, and mediated the direct effect of brain injury on reported compensation. Conclusion: Clinical and rehabilitation neuropsychologists often seek to have a better sense of how their patients perceive their compensatory behaviours. In practice, such an understanding is needed to help select appropriate methods and improve the long-term impact of rehabilitation programs: memory rehabilitation will fail if neuropsychologists do not deal, first and foremost, with the emotional and metacognitive issues surrounding traumatic brain injury, rather than focusing on cognitive efficiency.